2011
DOI: 10.1051/0004-6361/201116814
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of the extremely fast optical rebrightening of the afterglow of GRB 081029

Abstract: Context. After the launch of the Swift satellite, the gamma-ray burst (GRB) optical light-curve smoothness paradigm has been questioned thanks to the faster and better sampled optical follow-up, which has unveiled a very complex behaviour. This complexity is triggering the interest of the whole GRB community. The GROND multi-channel imager is used to study optical and near-infrared (NIR) afterglows of GRBs with unprecedented optical and near-infrared temporal and spectral resolution. The GRB 081029 has a very … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 50 publications
9
70
0
Order By: Relevance
“…3.4, we find the best-fit optical rise between 20 ks and 100 ks after the GRB trigger to be α reb ∼ −2.9. This high value is less extreme than α reb ∼ −8.2 and α reb ∼ −14 measured for GRB 081029 (Nardini et al 2011) and GRB 100621A (Nardini et al 2012;Greiner et al 2013), respectively, and agrees with both the typical values for FROAs reported (PV08) and with the late-bump rise steepnesses derived by Liang et al (2013) in their sample. Liang et al (2013) also found a good correlation between the optical luminosity at the rebrightening peak and the host frame peak time.…”
Section: Late Rebrighteningsupporting
confidence: 88%
See 4 more Smart Citations
“…3.4, we find the best-fit optical rise between 20 ks and 100 ks after the GRB trigger to be α reb ∼ −2.9. This high value is less extreme than α reb ∼ −8.2 and α reb ∼ −14 measured for GRB 081029 (Nardini et al 2011) and GRB 100621A (Nardini et al 2012;Greiner et al 2013), respectively, and agrees with both the typical values for FROAs reported (PV08) and with the late-bump rise steepnesses derived by Liang et al (2013) in their sample. Liang et al (2013) also found a good correlation between the optical luminosity at the rebrightening peak and the host frame peak time.…”
Section: Late Rebrighteningsupporting
confidence: 88%
“…Moreover, thanks to the rich coverage and the small uncertainties in the v, and u bands at ∼60 ks, we can identify the smaller-scale fluctuations around the rebrightening peak. Those wiggles are similar to the ones observed around the peak of the prominent optical rebrightenings of GRB 081029 and GRB 100621A discussed in Nardini et al (2011) and Greiner et al (2013), respectively. The late fading in the UVOT bands tracks the power-law decay observed in the bluer GROND bands well.…”
Section: Uvot Light Curvesupporting
confidence: 81%
See 3 more Smart Citations